Measurement of the tt[bar]Z and tt[bar]W cross sections in proton-proton collisions at √s=13 TeV with the ATLAS detector - Aaboud, Morad; Anders, Christoph; Andrei, George Victor; Antel, Claire; Baas, Alessandra Edda; Bolz, Arthur; Brandt, Oleg; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Geisler, Manuel Patrice; Giulini, Maddalena; et al. (Physical review, 2019)
A measurement of the associated production of a top-quark pair (t¯t) with a vector boson (W, Z) in proton-proton collisions at a center-of-mass energy of 13 TeV is presented, using 36.1 fb−1 of integrated luminosity collected by the ATLAS detector at the Large Hadron Collider. Events are selected in channels with two same- or opposite-sign leptons (electrons or muons), three leptons or four leptons, and each channel is further divided into multiple regions to maximize the sensitivity of the measurement. The t¯tZ and t¯tW production cross sections are simultaneously measured using a combined fit to all regions. The best-fit values of the production cross sections are σt¯tZ=0.95±0.08stat±0.10syst pb and σt¯tW=0.87±0.13stat±0.14syst pb in agreement with the Standard Model predictions. The measurement of the t¯tZ cross section is used to set constraints on effective field theory operators which modify the t¯tZ vertex.
Gesehen am 11.02.2020
Im Titel steht der Buchstabe "s" unter dem Wurzelsymbol
Im Titel steht jeweils der 2. Buchstabe t mit einem Oberstrich
ATLAS Collaboration: M. Aaboud, C. Anders, G.V. Andrei, C. Antel, A.E. Baas, A. Bolz, O. Brandt, D. Britzger, Dunford, D.E. Ferreira de Lima, S. Franchino, M.P. Geisler, M: Giulini, P. Hanke, J. Jongmanns, M. Kolb, A. Kugel, M. Lisovyi, H. Meyer zu Theenhausen, F. Napolitano, D.I. Narrias Villar, M. Sahinsoy, A. Schoening, H.-C. Schultz-Coulon, T. Spieker, R. Stamen, P. Starovoitov, S. Suchek, J. Wang, S. Weber, M. Wessels, X. Yue [und 2910 weitere]
Gesehen am 03.06.2020